Legal Responsibility For Residents Affected By Relocation In Development National Projects (Case Study of Kayan Hydropower Development) - Fanny Cathelia Erianto; Syamsul Hadi (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
The construction of the Kayan Hydroelectric Power Plant (PLTA) in North Kalimantan as part of the National Strategic Project (PSN) brings great benefits to the provision of clean energy and the acceleration of development, but raises socio-legal issues related to the relocation of the Dayak Kayan and Kenyah indigenous peoples in two villages upstream of the Kayan River. Relocation has led to the loss of customary land, livelihoods, and cultural heritage, raising questions about the government's form of legal responsibility. This research uses a juridical-normative method with a statutory and conceptual approach. The results of the study show that the government's responsibility is not only in the form of financial compensation or the provision of housing, but also includes socio-economic recovery, the provision of basic access, and the guarantee of livelihood sustainability. The state's obligations are divided into three aspects: respecting, protecting, and fulfilling the rights of citizens. Without the fulfillment of these responsibilities, relocation risks causing social conflicts, structural injustice, and a decline in the legitimacy of the PSN. Therefore, it is necessary to have a governance of relocation that is based on human rights, transparent, participatory, and in accordance with the General Principles of Good Governance (AUPB), so that the construction of the Kayan hydropower plant can run fairly, sustainably, and with social justiceThe abstract needs to summarize the contents of the paper and the research objectives.